Using Web 2.0 and Social Networking Tools in the K-12 Classroom. - Crane, Beverley E. (American Library Association, 2012)
Modern K-12 lessons should never be dull or rote. In today's classrooms, educators can engage their students using a wide range of digital and social networking tools, from wikis and blogs to podcasts and videoconferences. In this timely book, Crane brings together the best tools, ideas, examples, resources and lessons to help educators create unique and modern curricula to motivate their students.